Comparative study of viscose yarn properties spun with a softening device and pressure plate. Issue 23 (December 2019) - Liu, Keshuai; Xu, Duo; Wei, Jiang; Ni, Junlong; Yang, Shengming; Xu, Xiaoguang; Li, Wan; Zhang, Xinling; Deng, Bo; Xu, Weilin
In order to reduce energy consumption and further improve the performance of viscose yarns, this study introduced a collaborative control method to improve spun yarn performance by contacting the spinning strand with both a softening device and a pressure plate. In this study, we analyze the improving mechanism of spun yarn performance using the softening device and pressure plate. The results show that thermal insulation layer formed between the softening device and pressure plate could heat the yarns in all directions to further re-wrap out-exposed hairiness into the main body of yarns and save energy consumption. Four groups of 19.7 tex viscose yarns were spun with different collaborative apparatus (with and without the softening device or pressure plate). Four groups of viscose yarns were tested in terms of hairiness, unevenness, and tensile property. Moreover, the experimental results show that collaborative apparatus with the softening device and pressure plate could significantly improve yarn performance, including CV value, hairiness, break elongation, and breaking strength to 11.3%, 18.94, 12.9%, and 311.0 cN, respectively.